For what positive integer a is
3 2 + a + 3 2 − a
also an integer?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Chew-Seong Cheong - Nice solution ,
But you didn't account for the case where 4 − a = 1 when you assumed 3 4 − a ≤ 0
Also you can avoid the negative values of x as x 2 + 3 n ≥ 0 -:)
Let's assume N = ( 2 + a ) 1 / 3 + ( 2 − a ) 1 / 3
Cubing both side we get N 3 = 2 + a + 2 − a + 3 . ( 4 − a ) 1 / 3 ( ( 2 + a ) 1 / 3 + ( 2 − a ) 1 / 3 ) = > N 3 = 4 + 3 N ( 4 − a ) 1 / 3 = > ( N 3 − 4 ) 3 = ( 3 N ) 3 ( 4 − a )
Now the value of a will be such that there will be solution in N .The ( 4 − a ) should be a perfect cube.
First try with 4 − a = 1 = > a = 3 but this will not give any integral N .Now 4 − a = − 1 = > a = 5 this will give integral N .
So, the value of a = 5 .
Note There may exists other values of a which is not included in the solution.Any suggestion how to prove that this is only value of a ???
Good question. We require that a − 4 = n 3 for some positive integer n , so we're essentially looking for positive integers N , n such that
f ( N ) = N 3 + 3 n N − 4 = 0 .
Taking the domain of f as all reals for the moment, we have that
f ′ ( N ) = 3 N 2 + 3 n > 0 for any positive n , so there is precisely one root for any n . Also, f ( N ) > 0 for n , N > 1 , so I think that it's safe to conclude that the solution value a = 5 is unique.
Problem Loading...
Note Loading...
Set Loading...
Let x = 3 2 + a + 3 2 − a . Then, we have:
x 3 ⟹ x 3 = ( 3 2 + a + 3 2 − a ) 3 = 2 + a + 3 3 ( 2 + a ) 2 ( 2 − a ) + 3 3 ( 2 + a ) ( 2 − a ) 2 + 2 − a = 4 + 3 3 ( 4 − a ) ( 2 − a ) + 3 3 ( 2 + a ) ( 4 − a ) = 4 + 3 3 4 − a ( 3 2 − a + 3 2 + a ) = 4 + 3 3 4 − a x
For x to be an integer, 4 − a must be a perfect cube. For a > 0 , we note that the integral values of 3 4 − a ≤ 0 . Let n = − 3 4 − a . Then n is an non-negative integer. Therefore, we have:
x 3 x 3 − 3 3 4 − a x x 3 + 3 n x x ( x 2 + 3 n ) = 4 + 3 3 4 − a x = 4 = 4 = 4
Note that the possible values for x are − 4 , − 2 , − 1 , 1 , 2 , 4 and the only solution is when x = 1 , then x 2 + 3 n = 4 ⟹ n = 1 ⟹ 3 4 − a = − 1 ⟹ a = 5 .